Plasma Effect of Semiconductor Materials and Its Application in Optoelectronic Devices - Liu, Xingqi (International Journal of Materials Science and Technology Studies, 2026)
In this paper, the mechanism of plasma effect in semiconductor materials and its remarkable influence on the performance of optoelectronic devices are discussed in depth. Plasma effect, as a special physical phenomenon that can be excited in semiconductor, forms a high concentration of free electron and hole plasma state in semiconductor through high intensity illumination or electric field, thus significantly changing the optical and electrical properties of materials. In optics, the plasma effect enhances the nonlinear optical response of semiconductors and improves the ability of light absorption and refractive index control. In electricity, it changes the conductivity of semiconductors, optimizes the current-voltage characteristics, and may lead to self-organization phenomena such as the formation of quantum dots. In light-emitting diodes (LED), the plasma effect significantly improves the luminous efficiency, brightness and stability of LED by enhancing the radiation recombination process. In photodiode, plasma effect promotes the effective separation and transmission of photo-generated carriers, improves the response speed and sensitivity of the device, and optimizes the spectral response range. For solar cells, plasma effect is expected to further improve their photoelectric conversion efficiency by enhancing light absorption and improving charge separation efficiency. In addition, in the laser, the plasma effect also shows the potential to enhance the inversion of particle number in the gain medium and improve the stability of laser output.